Karakteristik Keluarga Balita dan Status Gizi Balita dengan Pneumonia di Puskesmas Moncek Kabupaten Sumenep - Sumarni, Sri; Rasyidah, Rasyidah (Indonesian Academia Health Sciences Journal, 2023)
Golden period is the peak period of child growth and development. Growth and development of toddlers need to be monitored regularly in order to produce quality human resources. At that age, a problem that is commonly called the Triple M Complex (Malnutrition - Morbidity - Mortality) can be found. Pneumonia is the main killer of children under five in the world. One of the growth indicators for toddlers is nutritional status. Nutritional status can be monitored using KMS. The high number of pneumonia cases in Indonesia is not only a disease problem but also related to behavior. Protection and prevention efforts must be followed by changes in the behavior of those closest to the child, especially parents. Parental behavior is influenced by many factors, such as education, age, occupation, parental marital status.to determine the characteristics of families of toddlers with pneumonia and the nutritional status of toddlers with pneumonia at the Moncek Health Center, Sumenep RegencyMethods: cross sectional analytic study with a purposive sampling technique From this study it was found that the percentage of female respondents was higher (96.7%) than male respondents (3.3%) as a parents.The most age of responden is 15-44 years (66,7%), almost all respondents were married as many as 27 people (90%). Characteristics of respondents based on education level is that most of them have elementary school education (33.3%) and most of them don’t go to work (33,3%). And from 30 toddler who get pneumonia are in negative growth nutritional status (100%).The nutritional status of children with pneumonia if based on the Towards Health Card (KMS) tends to "grow negative", that is, the body weight has decreased compared to the previous month's weight. Characteristics of families in toddlers with pneumonia are mostly of childbearing age, with female sex and most are housewives (not working) and almost half of them were elementary school graduates.